PENGARUH KARAKTERISTIK DEWAN DIREKSI DAN DEWAN KOMISARIS PERUSAHAAN TERHADAP SUSTAINABILITY REPORTING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2018) - Elsa Dwi Safitri; Aditya Septiani (Diponegoro Journal of Accounting, 2022)
The purpose of this research is to examine the effect of the characteristics of the board of commissioners and board directors characteristics on sustainability reporting in companies listed in Indonesia in 2018. This research used Manufacturing Company that listed o Indonesia Stock Exchange in 2018 as the research data. Stratified sampling method are used as a method for determining the sample, and obtained 157 companies as a sample. This research used logistic regression analysis with secondary data from manufacturing company annual report. The result of this research indicate a positive influence between size of board of commissioners and sustainability reporting. While for independent commissioners, female of board directors,national diversity board of directors have a negative effect on sustainability reporting.